Negotiating gender, body, and identity: Women’s experiences in nature lovers organizations and societal perceptions in Makassar - Nur Atikah Hijrah Maemunah R; Safriadi Safriadi (Priviet Social Sciences Journal, 2025)
This study explores how women engaged in adventurous activities within university-based nature lovers’ organizations in Makassar construct knowledge, interpret their bodies, and navigate societal perceptions. Employing a qualitative approach, this study draws on participant observations and in-depth interviews to examine women’s lived experiences in contexts traditionally dominated by men. The findings reveal that women’s knowledge manifests in three interconnected domains: understanding organizational culture and their motivations for joining; engaging in adventure education through experiential learning and skill development; and performing adventure activities while adapting to physical and social challenges. Women articulate the ambivalent meanings of their bodies, which they simultaneously view as obstacles requiring discipline and as sites of empowerment through training and resilience. Despite bodily changes that diverge from idealized feminine norms, these women continue to assert their identities as women, both through their appearance in public spaces and their preparation for field activities. This study highlights the complex negotiations of gender, body, and identity among women’s adventurers, situated within broader cultural constructions and societal expectations.